1,7х-(0,2х+2у)=? если 4у-3х=6 выразим уу=(6+3х)/4 подставим в 1 выражение<span>1,7х-(0,2х+2*(6+3х)/4)=1,7х-(0,2х+(6+3х)/2)=1,7х-0,2х-(6+3х)/2=1,5х-(3+х*3/2)=1,5х-3-1,5х=-3</span>1,7x-(0,2x+2y)упрощаем 1,7x-(0,2x+2y)= 1,7x-0,2x-2y=1,5x-2yиз 4y-3x=6 выражаем 1,5х через у подставляем в получившееся выражение 4y-3x=63х=4у-61,5х=2у-3 подставляем в выражение 1,5x-2y<span>2у-3-2у=-3 </span>
21*95+21*253 = 21*(95+253) = 21*348
Делится на 2; 2; 3; 7; 29
187*35-24*35 = 35*(187-24) = 35*163
Делятся на 5; 7; 163
39*53+39*17=39*(53+17) = 39*70
<span>Делится на 2; 3; 5; 7; 13</span>
55 :8 = 6(ост 7)
55 :9 = 6( ост 1)
Ответ: 55 плиток.
Вроде так))
A) z1+z2=1+i+1-i=2
z1-z2=1+i-1+i=2i
б)z1+z2=1+i-1-2i=-i
z1-z2=1+i-1+2i=3i
в)z1+z2=-i+1-i=1-2i
z12-z2=-i-1+i=-1